Financial regulatory harmonization in East Asia: Balancing domestic and international pressures for corporate governance reforms - Richard W. Carney (Asian Development Bank Institute (ADBI), 2011)
Is the harmonization of financial regulatory regimes possible in East Asia? Focusing on corporate governance, which many see as a critical part of the 1997 Asian financial crisis, and which is also seen as unresponsive to calls for change, this paper argues that such harmonization is possible, but that it will not be according to the best practices advocated by the International Monetary Fund, World Bank, Organisation for Economic Co-operation and Development, and other international organizations. At present, actors generally feign compliance with these international rules and standards. But this creates potential long-term problems by allowing distortions to persist and accumulate over time. By identifying the key actors that determine regulatory outcomes, this paper points to an alternative regulatory framework that would be adopted more comprehensively. This alternative framework is a compromise between the best practices advocated by international organizations, and the domestic political realities of East Asia.
Keywords: G32; G34; G38; P48; 330; Corporate Governance; Rechtsangleichung; Kapitalmarktliberalisierung; Wirkungsanalyse; Südkorea; Singapur; Japan